Circulating Irisin Is Reduced in Male Patients with Type 1 and Type 2 Myotonic Dystrophies - Dozio, Elena; Passeri, Elena; Cardani, Rosanna; Benedini, Stefano; Aresta, Carmen; Valaperta, Rea; Corsi Romanelli, Massimiliano; Meola, Giovanni; Sansone, Valeria; Corbetta, Sabrina (Frontiers in Endocrinology, 2017)
Context: Myotonic dystrophies (DM) are dominantly inherited muscle disorders characterized by myotonia, muscle weakness and wasting. The reasons for sarcopenia in DMs are uncleared and multiple factors are involved. Irisin, a positive hormone regulator of muscle growth and bone, may play a role. Objectives: To investigate 1) circulating irisin in a series of DM1 and DM2 male patients compared with healthy controls; 2) the relationships between irisin and anthropometric, metabolic and hormonal parameters. Design and study participants: This is a cross-sectional study. Fasting blood samples for glucometabolic, gonadic, bone markers and irisin were collected from 28 ambulatory DM1, 10 DM2 and 23 age-matched healthy male subjects. Body composition and bone mineralization (BMD) were measured by DEXA. Echocardiographic assessment and visceral adiposity, namely liver and epicardial fat, were investigated by ultrasound. Irisin released from cultured myotubes derived from 3 DM1, 3 DM2 and 3 healthy donors was assayed. Results: Plasma irisin levels were definitely lower in both DM1 and DM2 patients than in controls with no difference between DM1 and DM2. Irisin released from DM1 and DM2 myotubes was similar to that released from myotubes of the non-DM donors, though diabetic DM2 myotubes released more irisin than DM1 myotubes. There was no correlation between irisin and muscle strength or lean mass in both DM1 and DM2 patients. In DM1 patients, plasma irisin levels correlated negatively with oxygen consumption and positively with insulin resistance, while in DM2 patients plasma irisin levels positively correlated with fat mass at arms and legs levels. No correlation with visceral fat, left ventricular mass and gonadal hormones could be detected. In both DM1 and DM2 patients, legs bone mineral density parameters positively correlated with plasma irisin levels. Conclusions: Plasma irisin is reduced in both DM1 and DM2 male patients likely reflecting muscle mass reduction. Moreover, insulin resistance may contribute to modulation of plasma irisin in DM1 patients. The irisin-mediated crosstalk muscle-adipose tissue-bone may be active also in the male myotonic dystrophies’ model.